2022
DOI: 10.1177/13684302211070524
|View full text |Cite
|
Sign up to set email alerts
|

Privilege lost: How dominant groups react to shifts in cultural primacy and power

Abstract: As a function of their race, gender, class, and other social categories, long-standing privileges in social hierarchies have been afforded to some groups of people to the detriment of others. Recently, scholars have made considerable headway studying the social gains made by disadvantaged groups, including a better understanding of how relatively advantaged groups (e.g., White people; men) often pushback against and resist shifts in group-based power or prestige. The present body of work curates social psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…In addition, we encourage political psychologists to consider whether distinctiveness threat , power threat , and meritocratic threat each stem from a shared source—namely, the sense of status loss that follows from Whites’ demographic decline (Craig & Richeson, 2014; see also Hodson et al, 2022). Although we found that each of these threats explained unique variance in White identity, this pattern is also consistent with a view that each manipulation tapped into status threat, more generally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we encourage political psychologists to consider whether distinctiveness threat , power threat , and meritocratic threat each stem from a shared source—namely, the sense of status loss that follows from Whites’ demographic decline (Craig & Richeson, 2014; see also Hodson et al, 2022). Although we found that each of these threats explained unique variance in White identity, this pattern is also consistent with a view that each manipulation tapped into status threat, more generally.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies validate perceived demographic decline as a menacing stimulus with political consequences among Whites (Craig & Richeson, 2014; Danbold & Huo, 2015). Yet demographic decline has multiple implications for a dominant ingroup’s status, including a loss in cultural primacy and political power (Hodson et al, 2022). Seminal work (Craig & Richeson, 2014) teaches us that status threat—operationalized by perceived demographic decline—causes Whites to express defensive political reactions (i.e., conservative shift).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…These primarily right‐wing and conservative groups are frequently found to protest against migration policies and the demographic shift toward a more diverse society, holding hostile attitudes toward immigrants. Recent research suggests that those majority members perceive these growing ethnic groups as threatening and fear the loss of their and dominant status in the society (Brown et al, 2022; Craig et al, 2018; Hodson et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…While early collective action research focused mainly on disadvantaged groups and liberal goals, there is a growing body of research that has begun to analyse collective action form right‐wing and higher status groups (Becker, 2020; Choma et al, 2020). This research suggests that for example anti‐migration protests or protests against lower status groups have the goal to protect the group status against newcomers and thus to maintain intergroup inequalities (Brown et al, 2022; Çakal et al, 2016; Hasbún López et al, 2019; Hodson et al, 2022; Major et al, 2018; Shepherd et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation